THE EFFECT OF ENGLISH-LANGUAGE RESTRICTION ON SYSTEMATIC REVIEW-BASED META-ANALYSES: A SYSTEMATIC REVIEW OF EMPIRICAL STUDIES - Morrison, Andra; Polisena, Julie; Husereau, Don; Moulton, Kristen; Clark, Michelle; Fiander, Michelle; Mierzwinski-Urban, Monika; Clifford, Tammy; Hutton, Brian; Rabb, Danielle (International journal of technology assessment in health care, 2012)
Objectives: The English language is generally perceived to be the universal language of science. However, the exclusive reliance on English-language studies may not represent all of the evidence. Excluding languages other than English (LOE) may introduce a language bias and lead to erroneous conclusions. Study Design and Setting: We conducted a comprehensive literature search using bibliographic databases and grey literature sources. Studies were eligible for inclusion if they measured the effect of excluding randomized controlled trials (RCTs) reported in LOE from systematic review-based meta-analyses (SR/MA) for one or more outcomes. Results: None of the included studies found major differences between summary treatment effects in English-language restricted meta-analyses and LOE-inclusive meta-analyses. Findings differed about the methodological and reporting quality of trials reported in LOE. The precision of pooled estimates improved with the inclusion of LOE trials. Conclusions: Overall, we found no evidence of a systematic bias from the use of language restrictions in systematic review-based meta-analyses in conventional medicine. Further research is needed to determine the impact of language restriction on systematic reviews in particular fields of medicine.